PEMETAAN PROBLEMATIKA INTEGRASI PENDIDIKAN AGAMA ISLAM 222 DENGAN SAINS DAN TEKNOLOGI - Dwi Priyanto (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2016)
This paper is intended to map the problem of integration of Islamic Education (Pendidikan Agama Islam - PAI) with science and technology. It is expected, by this way, PAI is not only a vehicle for the transfer of religious knowledge, but also a planting of Islamic values that will be able to be applied by learners in public life as a Muslim. Hopefully, the Muslim will be able to play a role in solving the people and national problem and face the fast development of science and technology with all the impact. Ideally, integration of PAI with science and technology can be implemented as well as possible in an effort to establish Islamic religious education materials, and as a means of clarifying the problems that arise in the delivery of Islamic educational material that seems to be dogmatic at the beginning of Islam, as well as faith increasing to the truth of all that delivered Qur’an and Hadith. Tulisan ini ditujukan untuk memetakan problematika integrasi Pendidikan Agama Islam (PAI) dengan sains dan teknologi. Dengan cara ini diharapkan PAI tidak sekadar sebagai wahana transfer pengetahuan keagamaan semata, tetapijuga penanaman nilai-nilai keislamaan yang nantinya mampu diterapkan oleh peserta didik dalam kehidupan bermasyarakat sebagai seorang muslim. Diharapkan, muslim itu mampu berperan dalam menyelesaikan problem umat maupun bangsa menghadapi perkembangan sains dan teknologi yang begitu pesat dengan segala dampak yang ditimbulkan. Idealnya integrasi PAI dengan sains dan teknologi dapat dilaksanakan dengan sebaik-baiknya sebagai upaya dalam memantapkan materi pendidikan agama Islam, dan sebagai sarana memperjelas permasalahan yang timbul dalam penyampaian materi pendidikan agama Islam yang pada awalnya bersifat dogmatis, juga sebagai peningkatan rasa keimanan akan kebenaran segala yang disampaikan al-Qur’an dan Hadis.